Metabolism Energy and Viscosity in Response to Cold and Tropical Cereals Area in Leghorn Pullets - Saki, A.A. (International Journal of Poultry Science, 2004)
Environmental aspects could influence metabolism energy and viscosity of cereal in poultry nutrition. Four cereals seeds includes Alvand wheat, Makoie barley (as a cold cereals area), Chamran wheat and Karoun barely (as a tropical cereals area) in Iran were tested for measuring metabolize energy and viscosity. First experiment was arranged by 25 mature rooster using Sibbled methods to examine the metabolize energy. In the second experiment different percentage of cereals in 9 treatments (20 and 40% of Alvand and Makoie wheat and barley respectively) and (20 and 40% Chamran and Karoun, wheat and barley respectively) were used with control diets. The digesta of small intestine viscosity was recorded in the end of this experiment. No significant differences (P>0.05) was observed in gross energy (GE). Apparent metabolism energy (AME), apparent metabolism energy corrected by nitrogen (AMEn) True metabolism energy (TME) and TMEn were significantly higher in wheat than both types of barley. Significant increased (P